Doxorubicin induces cardiomyocyte pyroptosis via the TINCR-mediated posttranscriptional stabilization of NLR family pyrin domain containing 3. (November 2019) - Meng, Liping; Lin, Hui; Zhang, Jie; Lin, Na; Sun, Zhenzhu; Gao, Feidan; Luo, Hangqi; Ni, Tingjuan; Luo, Wenqiang; Chi, Jufang; Guo, Hangyuan
Abstract: Aims: Doxorubicin (DOX), a widely used powerful chemotherapeutic component for cancer treatment, can give rise to severe cardiotoxicity that limits its clinical use. Pyroptosis is characterized by proinflammation and has been defined as a new type of programmed cell death in recent years. However, whether the DOX-induced cardiotoxicity is related to pyroptosis, and if so, which genes are involved in this process is largely unknown. In this study, we sought to identify the effect of DOX on cardiomyocyte pyroptosis and further reveal the underlying regulatory mechanism. Methods and results: In vitro and in vivo experiments showed that DOX treatment induced cardiomyocyte pyroptosis as evidenced by increased cell death and upregulated expression levels of NLR family pyrin domain containing 3 (NLRP3), caspase-3, IL-1β, IL-18 and GMDSD-N. Inhibition of NLRP3 rescued the DOX-induced pyroptosis. qRT-PCR showed that TINCR lncRNA was upregulated by DOX treatment and knockdown of TINCR reversed the DOX-induced pyroptosis both in vitro and in vivo. Mechanistic investigations revealed that TINCR increased NLRP3 level via recruiting IGF2BP1 to enhance NLRP3 mRNA. And the effect of TINCR on cardiomyocyte pyroptosis was attenuated by the inhibition of NLRP3 or IGF2BP1. Finally, TINCR was not involved in DOX-induced pyroptosis in cancer cells. Conclusion: TINCR mediates the DOX-induced cardiotoxicity and pyroptosis in an IGF2BP1-dependent manner. Therefore, TINCR may serve as a promising therapeutic target to overcome the cardiotoxicity of chemotherapy for cancer therapy. Highlights: DOX treatment induced cardiomyocyte pyroptosis. TINCR lncRNA was upregulated by DOX treatment and knockdown of TINCR reversed the DOX-induced pyroptosis both in vitro and in vivo. TINCR increased NLRP3 level via recruiting IGF2BP1 to enhance NLRP3 mRNA.